2001
DOI: 10.1192/apt.7.6.469
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual syndrome: an update on definitions, diagnosis and management

Abstract: Most articles on the management of the premenstrual syndrome (PMS) begin by noting that the term “premenstrual tension” was first coined by R. T. Frank in 1931 and “pre-menstrual syndrome” by Greene & Dalton in 1953. However, in 1847, Dr Ernst F. von Feuchtersleben wrote: “The menses in sensitive women is almost always attended by mental uneasiness, irritability and sadness.” (quoted by Rubinow & Schmidt, 1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…The most common symptoms of the premenstrual syndrome are anxiety, depression, fatigue, nervousness, and irritability, feelings of loss of control, confusion, changes in sleep and appetite patterns, headache, breast swelling and tenderness, joint or muscle pains [4]. This syndrome have adverse effects on the life of women and hence, their daily activities at home, personal relationships, social activities, leisure time, sexual affairs, and their work efficiency will be affected by the syndrome [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms of the premenstrual syndrome are anxiety, depression, fatigue, nervousness, and irritability, feelings of loss of control, confusion, changes in sleep and appetite patterns, headache, breast swelling and tenderness, joint or muscle pains [4]. This syndrome have adverse effects on the life of women and hence, their daily activities at home, personal relationships, social activities, leisure time, sexual affairs, and their work efficiency will be affected by the syndrome [5].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we examined the extent to which CAT scores could detect clinically meaningful symptom change for PMS as defined by the National Institutes of Mental Health definition of 30% change from the 6 days prior to menses onset to days 5-10 after menses onset (29). For all three domains, approximately 60% of the women met this criterion based on the daily scores, and ROC analyses suggested moderate to high discrimination of the CATs.…”
Section: Discussionmentioning
confidence: 99%
“…For each woman, we calculated the percent change in daily scores from the late luteal (the 6 days before menses) to the follicular (days 5–10 of the cycle). 1 Following the National Institutes of Mental Health definition (29), a 30% symptom increase in the luteal phase was considered clinically meaningful, and women were categorized accordingly into groups with and without meaningful change. Receiver Operating Characteristic (ROC) analyses were then used to examine the extent to which changes in CAT scores from the pre- to the post-menstrual week accurately discriminated between the groups.…”
Section: Analysis Strategymentioning
confidence: 99%
“…Blake's study showed significant reductions in somatic symptoms such as breast tenderness and bloating, as recorded prospectively in diaries, in addition to psychological symptoms. They also highlight that the most robust changes seen were in specific PMS symptoms in comparison with depression or anxiety symptoms (having excluded patients suffering from significant psychiatric illness) [56].…”
Section: Cognition Behavioral Therapy (Cbt)mentioning
confidence: 97%